Preparation, evaluation and dissolution behaviors of water soluble drug loaded PLGA microspheres. - Nidhal Khazaal Marie (College of Pharmacy / Mustansiriyah University, 2008)
One of important drug delivery system is microencapsulation of bioactive agents using biodegradable polymers. Although a large number of studies, which utilizes PLGA have been performed, however, basic data and information upon drug release are in sufficient. Formulation of indomethacin sodium as microspheres using different percentages of PLGA by applying coacervation / phase separation and emulsification / solvent evaporation methods, were performed. The morphology, particle size and dissolution - release profile of the prepared microspheres have been studied. From both methods, it was noticed that the release of the drug is decreased as the amount of PLGA increased since it affects core: coat ratio. The microspheres prepared with low percentages of PLGA (not more than 20%) showed initial burst effect, which may suggest that erosion, is the major dissolution mechanism while diffusion might be the main mechanism for microspheres prepared with high percentages of PLGA. The shape of microspheres with > 30% PLGA (by coacervation method) has limited sphericity and larger particles size in comparison to that prepared with emulsification / solvent evaporation methods. Therefore, indomethacin - loaded PLGA microspheres (using 50% polymer) prepared by the second method can be used in the formulation of prolonged duration injectable dosage form.